Creating Awareness of Deadly Cytokine Storm to Common People and A Self Case Study: Pharmaceutical Science-Pharma - Baskaran, R.; Rajasekaran B, Ajay; Nithiya, A. M.; Aparna, A.M. (International Journal of Life Science and Pharma Research, 2022)
This review with case study covers the severity and hidden symptoms of cytokine storm that were missed in other articles. Most of the review studies focus on cytokine storm in a random way but this paper creates awareness to common people so that the intensity of the disease spreading can be minimized and fatality can be prevented. Cytokine storm is an umbrella term encompassing several disorders of immune disregulation. The symptoms, properties, mechanism and treatment methods for cytokine storm have been discussed along with preventive methods. Details about silent hypoxemia and its effects were also highlighted which are a major reason for not detecting this disease at early stages. This paper also describes a case of life-threatening cytokine storm caused by COVID-19 infection that was treated with clonal antibody and suppressed the cytokine release. This paper also highlights the importance of Vitamin D level in a body, which can suppress cytokines production by simultaneously boosting the innate immune system. Lesson learnt from this disease are elderly patients, especially males, with comorbidities, demonstrate increased susceptibility to poor prognosis or increased risk of severe condition or even fatality from COVID-19. Reports indicate that men appear to suffer more severe cases and die of the disease at greater rates than women, with deaths possibly up to 20 percent higher. This issue leads to future research and can work on the methods to increase the immunity of men to reach at least the immunity level of women so that fatality rate can be minimized. It has been concluded that if covid is left untreated, the cytokine starts releasing from the body and progress to extensive tissue damage, organ failure, and death.